Emulsifying properties of soy proteins: A critical review with emphasis on the role of conformational flexibility. Issue 12 (13th August 2017) - Tang, Chuan-He
ABSTRACT: Soy proteins as important food ingredients exhibit a great potential to be widely applied in food formulations, due to their good nutrition, functional properties and health effects. The knowledge about the structure–function relationships of these proteins is crucial for their applications, but still very scant, especially that on their molecular mechanism of emulsification. The purpose of this review is to present a comprehensive summary of the knowledge about emulsifying and interfacial properties of soy proteins, achieved during the past decades, and particularly to provide an insight in understanding the role of conformational flexibility in their emulsifying properties. The interplays between the emulsifying and interfacial properties are also elucidated. For these proteins, the conformational flexibility rather than the surface hydrophobicity is the crucial parameter determining their emulsification performance. On the other hand, evidence is fast growing to indicate that because of the insoluble nature, soy proteins are a kind of unique materials to perform as food-grade Pickering stabilizers. The knowledge about the Pickering emulsion stabilization is distinctly different from that for conventional emulsions stabilized by soy proteins. Thus, different strategies should be employed to develop soy proteins into a kind of effective emulsifiers, depending on the preference of emulsification performance or emulsion stability.